2011
DOI: 10.1188/12.onf.e49-e57
|View full text |Cite
|
Sign up to set email alerts
|

A Path Analysis: A Model of Depression in Korean Women With Breast Cancer-Mediating Effects of Self-Esteem and Hope

Abstract: Self-esteem and hope must be considered when developing services to reduce depression in Korean women with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
1
33
0
1
Order By: Relevance
“…No significant effect was observed on self-esteem. Previous studies have reported that self-esteem in Korean women with cancer was strongly related to family support Tae et al 2012). Lowered self-esteem commonly appears in patients with cancer (Berterö 2002).…”
Section: Discussionmentioning
confidence: 93%
“…No significant effect was observed on self-esteem. Previous studies have reported that self-esteem in Korean women with cancer was strongly related to family support Tae et al 2012). Lowered self-esteem commonly appears in patients with cancer (Berterö 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Hope may provide individuals a positive resource for combating depression and anxiety while protecting against perceptions of vulnerability and unpredictability [24]. Cancer survivors with higher levels of hope reported lower levels of depression and anxiety [45,46]. Optimism represents a positive attribution of success including positive emotions and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, health status, family support, and self-esteem of women with breast cancer have been shown to indirectly affect depression through hope. (22) There are few studies employing interventions to improve hope. (23,24) However, a recent study analyses a randomized clinical trial of women who had undergone mastectomy, aiming to assess the effects of a spiritual support intervention on spirituality and clinical parameters.…”
Section: Discussionmentioning
confidence: 99%